Urban Farming Program For Women PKK Manang Village To Improve Family Food Security Value In The Era Of The Pandemi Transition Covid-19 - Wahyu Adhi Saputro; Musta’in; Ahmad Fauzi (Fakultas Hukum, UPN Veteran Jawa Timur, 2020)
Food is indeed one of the mandatory things that must be fulfilled. However, the current condition of the population growth which continues to increase is not accompanied by an increase in agricultural land so that the available food stock may one day be insufficient. This makes a food problem which is closely related to food security. PKK mothers are people who think about food for their families so that they have a huge influence. The decline in the amount of land and reduced food stocks in the era of the Covid-19 pandemic because people flocked to buy large amounts of food stocks became a problem that was raised in this community service program. The aim of this program is to introduce urban farming methods that can be done in empty house areas to increase food access to increase the value of family food security. The method used in the community service program was the online extension method and then carried out the urban farming practice which was carried out by one of the PKK mothers in Manang Village. It is hoped that this example can become a role model for the people around him. The results of the community service program that have been carried out have improved the skills of PKK Manang Village women in cultivating plants in the area of ​​their home yard that is still empty or not in use. The existence of planting crops that can be harvested can meet food needs so that from the dimension of accessibility to food security it can be fulfilled properly.